The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1091/mbc.e12-07-0499
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Vs organize actin cables in fission yeast

Abstract: In fission yeast, myosin Vs contribute to actin cable extension through the cell and promote retrograde flow. Chimeric motor proteins are used to show that Myo52 organizes actin cables by both delivering cargoes to cell tips and exerting physical force pulling on the cables. This suggests that cable tracks are shaped by cargo transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(90 citation statements)
references
References 58 publications
5
80
1
4
Order By: Relevance
“…Some actin filaments and small bundles of filaments persisted on the lateral borders of rings throughout constriction (Figure 1A arrow) [26, 29]. Myo51 localized along For3p-dependent actin cables during interphase [23] giving a filamentous appearance in the cytoplasm (Figure 1A arrow). Beginning at time zero Myo51p concentrated in a narrow equatorial band and in filamentous structures between nodes [30] around the middle of the cell (Figures 1A asterisk and 1B), both dependent on actin filaments [23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some actin filaments and small bundles of filaments persisted on the lateral borders of rings throughout constriction (Figure 1A arrow) [26, 29]. Myo51 localized along For3p-dependent actin cables during interphase [23] giving a filamentous appearance in the cytoplasm (Figure 1A arrow). Beginning at time zero Myo51p concentrated in a narrow equatorial band and in filamentous structures between nodes [30] around the middle of the cell (Figures 1A asterisk and 1B), both dependent on actin filaments [23].…”
Section: Resultsmentioning
confidence: 99%
“…Myo51 localized along For3p-dependent actin cables during interphase [23] giving a filamentous appearance in the cytoplasm (Figure 1A arrow). Beginning at time zero Myo51p concentrated in a narrow equatorial band and in filamentous structures between nodes [30] around the middle of the cell (Figures 1A asterisk and 1B), both dependent on actin filaments [23]. Myp2 began to accumulate in fully formed contractile rings at time +20 min (Figures 1A asterisk and 1B) [25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After switching to medium containing 2% 2-DG, actin cables can still be observed in bni1-11 bnr1 Δ cells at 35 °C (Figures 4E and 4F), indicating that actin polymerization is not necessary for cable stabilization. Additionally, it has been shown that myosin Vs contributes to actin cables organization in fission yeast [28]. Since Myo2 is immobilized on actin cables upon glucose depletion, it is possible that Myo2 helps to stabilize them.…”
Section: Resultsmentioning
confidence: 99%